Code-switching in EFL Classroom Settings: A Review from Teachers’ and Students’ Outlook - Fauzi, Iwan (Journal of English Teaching and Learning Issues, 2023)
The use of code-switching in English-as-a-foreign-language (EFL) classrooms has considerably occupied serious discussions. Most language researchers consider whether to use only the target language exclusively or to use it alongside the first language in foreign language classrooms. This paper reviews 15 empirical studies investigating code-switching in different EFL classroom settings and cultures regarding English as a second and foreign languages. There are three main things that this paper wants to seek for the answer from those studies viewed from teachers’ and students’ outlooks; those are the perception, the function, and the strategy to generate learning success from code-switching. The results show that code-switching provides the chance for the lower proficiency level of English learners to feel secure in expressing what they want to speak, but not for those who belong to high proficiency level ones. Besides, code-switching tends to function as classroom management, but the over-functioning of code-switching in the EFL classroom can only hinder learners from receiving comprehensible input of English. Of all, the most important highlight from this paper is that the more the mother tongue is used the worse the success of learning English.